2023
DOI: 10.3390/coatings13091604
|View full text |Cite
|
Sign up to set email alerts
|

Active Broadband Absorber Based on Phase-Change Materials Optimized via Evolutionary Algorithm

Jing Ma,
Yonghong Tian,
Jingyi Cheng
et al.

Abstract: This article proposes a temperature-controlled absorber based on VO2, which consists of five layers: a disk-shaped VO2 layer array, a dielectric layer, a circular hole VO2 array, a SiO2 layer, and a gold substrate from top to bottom. We optimized the thickness of the other four layers of the absorber, except for the gold layer, using PSO. After ten iterations, we determined that the optimal parameters for the top-to-bottom four-layer thicknesses were 0.183 μm, 0.452 μm, 0.557 μm and 1.994 μm. At this point, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Even if it could be manufactured, the cost would be very high -the process tolerance of the device will be discussed later. 50 First we discuss the effect of the thickness of the layer d. See Fig. 4(a), from which it can be observed that the absorption curve is blue-shifted when d is increased from 5 mm to 11 mm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if it could be manufactured, the cost would be very high -the process tolerance of the device will be discussed later. 50 First we discuss the effect of the thickness of the layer d. See Fig. 4(a), from which it can be observed that the absorption curve is blue-shifted when d is increased from 5 mm to 11 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Even if it could be manufactured, the cost would be very high – the process tolerance of the device will be discussed later. 50 First we discuss the effect of the thickness of the dielectric layer d . See Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In practical application, the incident waves may come from different directions and the polarization state is not fixed. 52,53 Therefore, the design of absorptive devices should take into account the influence of polarization and incident angle on the absorption performance. To demonstrate the practicality of our absorption device, we performed a parametric scan simulation for incident angles from 0° to 60° with a step size of 10° under TM and TE modes at T = 342 K to reflect the sensitivity of the device to the incident angle.…”
Section: Calculation and Discussionmentioning
confidence: 99%
“…Recently, some MMs integrated with VO 2 have been proposed to achieve adjustable functions. 14,34–38 For example, Yang et al proposed a switchable quarter-/half-wave plate that can achieve multiple plasmon resonances by adjusting the phase transition of VO 2 . 39 Wang et al theoretically designed an absorber that can be continuously adjusted.…”
Section: Introductionmentioning
confidence: 99%